Impact of group dancing during Japanese festivals on people’s sense of community - Kawase, Satoshi; Eguchi, Kei (Frontiers in Psychology, 2025)
Moving together or attending festivals has been reported to foster social bonding. However, whether festivals with and without dancing affect individuals’ social bonds and sense of community remains unclear. The existing research does not demonstrate whether lasting effects exist over time, even when community festivals are held only a limited number of times a year. To address this issue, this study examines the impact of dancing at local festivals on individuals’ sense of community. This study hypothesized that if dancing with others enhances social bonding, individuals’ participation in festivals may enhance sense of community since dancing is a part of many festivals. Accordingly, an online survey was conducted a few months after a community festival, and participants responded to three scales: the Brief Sense of Community Scale, Community Consciousness Scale, and UCLA Loneliness Scale. The results found (1) that the participants who attended and danced at a festival with dancing showed a higher sense of community and lower loneliness level than those who did not dance or those who attended a festival without dancing. (2) Previous festival attendance habits did not influence these tendencies. (3) Furthermore, these tendencies were not related to the individual’s willingness to attend festivals. Therefore, dancing at festivals may promote a greater sense of community than attending festivals without dance.